2020
DOI: 10.1080/1461670x.2020.1852885
|View full text |Cite
|
Sign up to set email alerts
|

“Be Less of a Slave to the News”: A Texto-Material Perspective on News Avoidance among Young Adults

Abstract: The distinct media repertoire of young adults in the digital age, especially their increasing ability to bypass the news media, inspires a wealth of research. While previous studies have focused on social-and content-related motivations to avoid the news, we have yet to fully understand the interplay of such motivations with material, technology-related considerations. Drawing on 36 in-depth interviews with Israeli young adults, this paper explores the varied motivations of young audiences to avoid the news th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 30 publications
0
20
0
1
Order By: Relevance
“…Avoiding hopelessness (Woodstock 2014) or "overwhelming feelings of compassion towards news of human suffering" (Helgerud 2017, 1) are found to be important motivations for news avoidance also in some of the already mentioned studies, which further outline user strategies for prioritizing time and attention for important caretaking responsibilities (e.g., Toff and Palmer 2019). A recent study (Aharoni, Kligler-vilenchik, and Tenenboim-Weinblatt 2020) productively differentiates between content-related, medium-specific or user-oriented motivations for news avoidance. This study, as well as a few other contributions (e.g., Meijer and Groot Kormelink 2021) frame avoidance as part of broader practices of navigating news.…”
Section: Monitoring and Avoiding News In The Attention Economymentioning
confidence: 97%
See 1 more Smart Citation
“…Avoiding hopelessness (Woodstock 2014) or "overwhelming feelings of compassion towards news of human suffering" (Helgerud 2017, 1) are found to be important motivations for news avoidance also in some of the already mentioned studies, which further outline user strategies for prioritizing time and attention for important caretaking responsibilities (e.g., Toff and Palmer 2019). A recent study (Aharoni, Kligler-vilenchik, and Tenenboim-Weinblatt 2020) productively differentiates between content-related, medium-specific or user-oriented motivations for news avoidance. This study, as well as a few other contributions (e.g., Meijer and Groot Kormelink 2021) frame avoidance as part of broader practices of navigating news.…”
Section: Monitoring and Avoiding News In The Attention Economymentioning
confidence: 97%
“…Adapted from the typology developed by Aharoni, Kligler-vilenchik, and Tenenboim-Weinblatt (2020) of content-based, medium-based or user-oriented avoidance, we find it fruitful to characterize avoidance strategies found in our material as either time/ activity-based or medium/content-based.…”
Section: Management Strategies: Intensified Monitoring Strategic Avoidancementioning
confidence: 99%
“…The country-specific supply of news can contribute particularly to cognitive news avoidance. For example, in Israela news-saturated culturethe burden generated by the intense coverage of an ongoing, polarizing political crisis alongside the sense of obligation to stay informed have mutually shaped people's news avoidance practices and motivations (Aharoni et al, 2021). In the case of the US, a salient trend in news supply affecting news avoidance might be what Benkler, Faris and Roberts (2018) examine in terms of asymmetric polarization.…”
Section: Discussionmentioning
confidence: 99%
“…These include both the information environments and the collective values, perceptions, and norms shared around them (Toff and Kalogeropoulos 2020). For instance, in a study conducted in Israel, times of crisis were found to motivate both heavy and light consumers to temporarily circumvent the news (Aharoni, Kligler-Vilenchik, and Tenenboim-Weinblatt 2021). In a turbulent context of an ongoing violent conflict, some news avoidance motivations seem to go beyond individuals' content preferences and demonstrate a cultural prism for news avoidance.…”
Section: Understanding News Avoidance Across Different National Contextsmentioning
confidence: 99%
See 1 more Smart Citation